2018
DOI: 10.1007/s40744-018-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Advances Using Tocilizumab in the Treatment of Rheumatic Diseases

Abstract: Tocilizumab (TCZ) is the first humanized antiinterleukin-6 (IL-6) receptor monoclonal antibody approved for the treatment of patients with rheumatoid arthritis (RA), Castleman's disease, polyarticular and systemic juvenile idiopathic arthritis, and, most recently, giant cell arteritis as well as for the treatment of chimeric antigen receptor T cell therapy-induced cytokine release syndrome. The global clinical development program for TCZ provides a wealth of clinical data on intravenous TCZ, and more recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 121 publications
1
78
1
10
Order By: Relevance
“…Consistent with expectations for a biologic DMARD for RA, serious infections, including serious bacterial infections, are among the most common serious adverse events reported in clinical trials, post-marketing surveillance studies, short-term studies and open-label extension studies. The overall rate of serious infections in patients with long-term exposure to IL-6 pathway inhibitors is in line with rates seen in studies with a short duration of exposure 58,145,159,161,[164][165][166][167][168][169] .…”
Section: Safety Of Il-6 Inhibitionsupporting
confidence: 68%
“…Consistent with expectations for a biologic DMARD for RA, serious infections, including serious bacterial infections, are among the most common serious adverse events reported in clinical trials, post-marketing surveillance studies, short-term studies and open-label extension studies. The overall rate of serious infections in patients with long-term exposure to IL-6 pathway inhibitors is in line with rates seen in studies with a short duration of exposure 58,145,159,161,[164][165][166][167][168][169] .…”
Section: Safety Of Il-6 Inhibitionsupporting
confidence: 68%
“…It was reported that IL6 À/À mice exhibited delayed aseptic skin wound healing (Gallucci et al, 2000;Lin et al, 2003) and recombinant murine IL-6 improved skin wound healing in glucocorticoidtreated mice (Gallucci et al, 2001). In contrast, excess IL-6 causes inflammatory diseases; therefore, IL-6 receptor antibody (Tocilizumab) has been used as therapeutic agent against Castleman disease and rheumatic diseases in the clinic (Rubbert-Roth et al, 2018;Yoshizaki et al, 2018). Taken together, it appears that precise regulation of IL-6 levels is necessary at inflamed sites to regulate inflammation and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…A humanized monoclonal antibody viz. tocilizumab competitively binds to IL-6 receptors and subsequently prevents the binding of IL-6 to its receptor [130]. Notably, the blocking of the IL-6…”
Section: Development Of Antiviral Therapeuticsmentioning
confidence: 99%